Wireless power transfer for electric vehicle - Sabki S.A.; Tan N.M.L. (IEEE Computer Society, 2023)
In this paper, a review of existing wireless power transfer solutions used in electric vehicle battery charger are provided. The different levels of battery charger are discussed based on the recommended practice by SAE J-113. The concept for each solution is reviewed and evaluated considering the performance of battery charger, power electronic limitations and the circuit topologies. Furthermore, the credits and disadvantages of the wireless power transfer technologies, compensation and power electronics requirement for electric vehicle are discussed and compared in detail. Finally, a proposed circuit topology for resonant inductive wireless charging is presented. © 2014 IEEE.